The Image of the Mathematics Teachers in High School Students - Carlos Alberto Juárez-Moreno; José Antonio Juárez-López; Lidia Aurora Hernández-Rebollar (REDIMAT, 2025)
This study aims to explore the perceptions of high school students at risk of academic failure regarding their mathematics teachers, using drawings and related questions to gather detailed information. The perception of these students can provide valuable insights into the potential role of teachers in students’ academic failure. Analyzing the meanings behind the drawings is crucial for addressing challenges associated with negative images that students may have of their mathematics teachers. The close relationship between the drawings and the personal experiences of students highlights the significant influence of this task on individual perceptions of mathematics teaching.